Hadith #1295 - Sunan al-Nasa'i - Abdullah bin Abi Talha; Abdullah bin Mubarak عبد الله بن المبارك; Abu Talha Ansari; Hammad bin Salama حماد بن سلمة; Sulaiman Mwla al-Hasan bin Ala سليمان مولى الحسن; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan al-Nasa'i)
“We said: ‘O Messenger of Allah (ﷺ), we know how to send salams upon you, but how should we send salah upon you?’ He said: ‘Say: “Allahumma salli ‘ala Muhammadin ‘abdika wa rasulika kama salaita ‘ala Ibrahim wa barik ‘ala Muhammadin wa ‘ala ali Muhammadin kama barakta ‘ala Ibrahim (O Allah, send salah upon Muhammad, Your slave and Messenger , as You sent Salah upon Ibrahim, and send blessings upon Muhammad and upon the family of Muhammad as You sent blessings upon Ibrahim
Grade: